A cross-country analysis on the impact of tourism on threatened plant species - Habibullah, Muzafar Shah; Din, Badariah; Choo, Wei Chong; Radam, Alias (Elsevier, 2016)
This study used a sample of 106 countries to investigate the link between the number of threatened plant species and tourism which was proxied by the number of international tourist arrivals. In the analysis, we also include GDP per capita, population growth, and land under crop, which act as the control variables. We find that using OLS, the number of international tourist arrivals, population growth rate and land cultivated with crop increases the number of threatened plant species, while GDP per capita reduces the number of threatened plant species. Our further analysis using quantile regression indicates that tourism affected positively the number of threatened plant species for all quantiles (0.05 0.25 0.50 0.75 0.90 0.95); crop production (positively) at middle quantiles (0.50 0.75); GDP per capita (negatively) at lower quantiles (0.05 0.25); and population growth (positively) at middle quantiles (0.50 0.75). Our analysis clearly indicates that using estimates from OLS may have serious “bad” policy implications on the number of threatened plant species, compared to the quantile method that can capture properly the dimension of the threatened plant species. As for tourism, our study supports the effort for biodiversity conservation and sustainable tourism worldwide.